MiR164–NAC21/22 module regulates the resistance of Malus hupehensis against Alternaria alternata by controlling jasmonic acid signaling. (May 2023) - Zhou, Tingting; Cao, Lifang; Hu, Kaixu; Yu, Xinyi; Qu, Shenchun
Abstract: Apple leaf spot disease caused by Alternaria alternata apple pathotype ( A. alternata AP) is one of the most severe fungal diseases affecting apple cultivation. Transcription factors are involved in various disease-resistance responses, and many of them are regulated by miRNAs. Here, we performed RNA-Seq to investigate gene expression changes during the defense response of Malus hupehensis against A. alternata AP. NAC21/22 was induced upon A. alternata AP infection and silenced by miR164 via direct mRNA cleavage. Contrasting expression patterns were noted between mature miR164 and NAC21/22 during infection. Contrary to NAC21/22 silencing, transiently overexpressing NAC21/22 in M. hupehensis alleviated disease symptoms on 'gala' leaves, impeded A. alternata AP growth, and promoted jasmonic acid (JA) signaling-related gene expression. Importantly, transient miR164f overexpression in 'gala' leaves enhanced A. alternata AP sensitivity, due perhaps to NAC21/22 downregulation, whereas miR164 suppression produced an opposite effect. In summary, the miR164– NAC21/22 module plays a pivotal role in apple resistance against A. alternata AP by regulating JA signaling. Highlights: MhNAC21/22 is induced by A. alternata AP infection. MhNAC21/22 positively regulates the resistance of 'gala' to A. alternata AP. MhNAC21/22 is regulated by miR164 via directly cleavage. miR164f negatively regulates of the resistance of 'gala' to A. alternata AP. The miR164 - NAC21/22 module modulates JA signaling pathway .